Resistensi Budaya Tahlilan Pada Masyarakat Pragaan Daya: Kajian Living Hadis - Siti Rahmah; Esya Heryana; Ach Badry (Jurnal Riset Agama, 2022)
This study aims to diccus the resitanse of tahlilan culture in the Pragaan Daya community. Researchers uncover this problem based on field facts that exist in the Pragaan Daya community. This study uses observation data, interviews with a number of informants, and several other literature sources. To process the data, this research uses a living hadith approach as a way to obtain data. The results and discussion of this study indicate that there is perspective on prohibition of hadith law related to tahlilan culture, community responses related to tahlilan cultural law and hadith views on tahlilan and traditional values. This study concludes that tahlilan has existed since the time of prophet Muhammad Saw. Based on available references and the hadith of the prophet Muhammad Saw. shows that the law of giving food treats to people who come to the house of the mortician without being based on the  shari’ah then the law is haram as the prophet’s hadith for the prohibition. This study recommends academics and research to develop further related to tahlilan cultural resistance in the Pragaan Daya community through a theological perspective.